Parameter Penyelesaian Delik Adat Melalui Keadilan Restoratif Berdasarkan Kitab Undang-Undang Hukum Acara Pidana - Boydo Saragih (Journal of Global Legal Review, 2026)
The enactment of the New Criminal Code (KUHP) materially acknowledges the existence of customary criminal law (living law), which aligns with the Restorative Justice mechanism in the New Criminal Procedure Code (KUHAP). However, the absence of objective material parameters within the criminal justice system leaves state law vulnerable to biased recognition of customary law, risking power imbalances, double jeopardy, and mob justice. This study aims to formulate a conceptual framework as a material boundary in examining the validity of customary offense settlements. Using a normative legal research method with statutory and conceptual approaches, this study proposes the doctrinal concept of the "Tripartite Parameter". The findings indicate that the settlement of customary offenses can only be accommodated by the national legal system if it passes three testing pillars: (1) Authoritative validation of material legality through legitimate customary institutions; (2) The doctrine of absolute consent (veto right) for victims to ensure pure voluntariness without majority intimidation; and (3) The proportionality limit of sanctions, which must be restitutive-educative and free from physical torture or absolute impoverishment. This parameter is offered as a theoretical instrument for the development of national law, ensuring that the integration of restorative justice upholds constitutionalism and human rights without negating local wisdom.